Changes in the Chemical Properties of a Soil Impacted by Intensive Agriculture, North-eastern Mexico - Silva-Arredondo, F.; Moreno, M. Pando; Gonzalez Rodriguez, H.; Morales, L. Scott (International Journal of Bio-resource and Stress Management, 2023)
The present study was carried out in a semi-arid area within the Chihuahuan Desert in the Northern Mexican Plateau. The objective of the study was to evaluate the long term changes in the soil chemical properties after one cycle of potato cultivation with intensive application of agrochemicals.Sampling sites were established in areas that had1, 2, 5 and 10 years of abandonment after potato cultivation and an area of native grassland was also considered as control. Potato cultivation is carried out by a company that rent the land to the peasants, so cultivation is done in the same way all over this area. At each site, the following variables were evaluated at 0-10 and 10-30 cm soil depths: pH, CEC, EC, SOM,CaCO3, CaSO4, Na, K, Mg, P, total N, Ca, Cu, Fe, Mn and Zn. Results showed that even though sites were statistically equal for all the evaluated variables, there were some variables (total N, extractable P, Mg, Cu and Zn) that fell in different ranges according to the Mexican NOM-021-SEMARNAT- 2000 of soil classification.